ANALISIS KEMAMPUAN PEMECAHAN MASALAH MATEMATIS PESERTA DIDIK DALAM MENYELESAIKAN SOAL MATERI MATRIKS BERDASARKAN TEORI WANKAT DAN OREOVOCZ - Ana Rajiyatul Muna; Sugiyanti; Nurina Happy; Fairuz Amin (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
The purpose of this study is to analyze the mathematical problem-solving abilities of students in working on matrix material problems based on the theory of Wankat and Oreovocz with 7 stages of problem-solving strategies. The seven problem- solving stages are: the